Movements beyond human: Ecological aesthetics and knowledges in underwater wildlife documentaries - Heidi Mikkola (The Finnish Society for Human-Animal Studies, 2022)
Our conceptions of underwater space are mostly based on images we have seen of it. These images, mediated through technology, have a great impact on how the environment is perceived. The article analyses how three different wildlife documentary series (Planet Earth, Dolphins – Spy in the Pod and Oceans) produce an oceanic environment and its inhabitants, and how these cinematic environments can affect how the ocean is perceived. The article’s approach questions anthropocentrism and maps the relation between cinematic features, the oceanic environment and the aesthetic possibilities of perceiving more-than-human space. The analysis emphasises how the films’ aesthetics are connected to the material movements of environments and animals. With the help of Gilles Deleuze’s and Félix Guattari’s concepts of assemblage and deterritorialisation, the article takes a posthumanist approach in mapping the possibilities of decentering the human and engaging non- human animals and nature as the proper cinematic subjects. The article argues that the audiovisual aesthetics of the analyzed documentaries are able to challenge anthropocentrism, but at the same time they are anthropomorphic in premissing their imagery on human comprehensibility.